Evaluation of the BioPlex™ 2200 ANA Screen: Analysis of 510 Healthy Subjects: Incidence of Natural/Predictive Autoantibodies - SHOVMAN, O; GILBURD, B; BARZILAI, O; SHINAR, E; LARIDA, B; ZANDMAN-GODDARD, G; BINDER, S R; SHOENFELD, Y (Annals of the New York Academy of Sciences, 2005)
: The BioPlex™ 2200 ANA Screen is a fully automated system that determines levels for 13 different autoimmune antibodies of established clinical significance. The objective of this study was to determine the specificity of the BioPlex™ 2200 ANA Screen assay and to analyze the antibody profile samples collected from healthy subjects against comparative ELISA and IIF screening methods. A total of 510 specimens were randomly selected from a cohort of apparently healthy blood bank donors. Samples were distributed to five age brackets. All samples were tested using Bio‐Rad's ANA Screen kit. Specificity was compared to IIF and ELISA results. Most of the samples were found negative in all ANA screening systems (84.5% by IIF, 92.5% by BioPlex™ 2200 ANA Screen kit, and 94.5% by ELISA). The frequency of positive results was highest (15.5%) using IIF, in comparison to almost similar results (5.5% vs. 7.5%) achieved by ANA ELISA and BioPlex™ 2200 ANA Screen kits. The positive rate of autoantibodies was significantly reduced when analyzed by different combinations of ANA screen assays (from 2.35% using IIF + BioPlex ANA Screen tests to 0.98% by using all three tests). Using the BioPlex™ 2200 ANA Screen system, we were able to identify samples with high levels of individual antibodies: anti‐dsDNA at 20‐63/IU/mL, antichromatin at 4–8 AI, anti‐SmRNP at 2–6 AI, and anti‐RNPA at 2‐4.5 AI. Importantly, from 7 IIF and ELISA positive sera, 5 of these were also BioPlex 2200 positive, suggesting that the BioPlex is seeing the samples that are of the greatest interest, using the established techniques. The specificity of the BioPlex 2200 ANA Screen analysis of 13 different analytes (dsDNA, centromere B, chromatin, Jo1, ribosomal P, RNP 68, RNP A, Scl‐70, Sm, SmPNP, SS‐A52, SS‐A60, SS‐B) is comparable (P < 0.252) to the ELISA ANA screening test. Like the ELISA, the BioPlex 2200 has a lower (P < 0.001) positive rate than IIF for the autoantibody screening.